Gardens of philosophy : Ficino on Plato - Ficino, Marsilio, 1433-1499 (Commentaries by Ficino on Plato's writing., 2006)
Under the patronage of the Medici family, Marsilio Ficino translated into Latin and commentated on the meaning and implications of key works by Plato--including 25 of Plato's dialogues and 12 letters ascribed to the philosopher. The 40 concise articles in this collection comprise the first English translation of Ficino's works and provide an insightful glimpse into the philosophy that contributed to the Renaissance.